Pelatihan Microsoft Office 365 bagi Guru Sekolah Dasar di Klaten - Suwartini, Sri; Rahmawati, Isna; Zudhah Ferryka, Putri; Rofisian, Nela (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2022)
This community service in the form of Microsoft Office 365 training aims to introduce digitalmedia in the learning process in elementary schools. They learned using page links andvarious media in elementary schools, including sound, images, and videos. Thus learningactivities become more meaningful, and learning resources become multi-content.Participants in this service consist of elementary school teachers in Klaten. Various methodsare used to implement this Microsoft Office 365 training. The methods are demonstration,mentoring, and discussion. Four materials are given in the Microsoft Office 365 training:Form, OneNote, ClassNote, and Sway. The results of this service activity show success inmastering the four materials by the trainees. This can be seen from the high enthusiasm inevery stage of the training implementation.